Use of tristimulus reflectance colorimetry for detection of fresh milk adulteration with reconstituted dry milk - D. S. Myagkonosov; E. V. Topnikova; D. V. Abramov; O. G. Kashnikova (Пищевые системы)
The authors propose a method for disclosing the adulteration of natural fresh milk by adding powdered milk, based on a quantitative assessment of the content of products of the initial stage of the Maillard reaction, which are a specific indicator of the presence of powdered milk. Implementation of the method involves isolation from milk of the preparation of dry, lactose-purified casein, followed by heat treatment under strictly controlled conditions. These conditions include maintaining a moisture level of approximately 6 % and a temperature of 100 ± 1 °C for five hours. In the process of heat treatment, the transformation of uncolored products of the initial stage of the Maillard reaction (lactosylated amino groups of amino acids) into melanoids characterized by intense coloration takes place. The color intensity of melanoids can be measured using a colorimeter and represented in color space coordinates CIE L*a*b*. The concentration of melanoid pigments can be determined using both the standard criterion of total color difference (ΔE) and the complex criterion (KCh) proposed by the authors, which is calculated as the ratio of Chroma and Hue values. The criterion KCh demonstrates a higher accuracy in describing the relationship between the staining intensity of the sample and the mass fraction of milk powder protein in the mixture compared to the standard criterion ΔE. The developed colorimetric method makes it possible to detect the addition of dry powdered milk at the level of approximately 5 grams per 1 liter of fresh natural milk.